Nitrogen-doped graphene and conducting polymer PEDOT hybrids for flexible supercapacitor and electrochemical sensor. (20th September 2020) - Teng, He; Song, Jingyao; Xu, Guiyun; Gao, Fengxian; Luo, Xiliang
Highlights: Free-standing NG/PEDOT hybrids film with better hydrophilicity, conductivity, and good electrochemical capacitance is gained. The hybrids film serves as electroactive material, current collector, and mechanical support simultaneously for fabricating flexible supercapacitor. The supercapacitor shows high specific capacitance, flexibility, and outstanding stability. The NG/PEDOT hybrids-based sensor presents high sensitivity for dopamine detection. Abstract: Nitrogen-doped graphene (NG) materials are highly desired for supercapacitors and sensors. Herein, we report nitrogen-doped graphene and conducting polymer PEDOT hybrids for the study of flexible supercapacitor and electrochemical sensor. Free-standing NG/PEDOT hybrids film electrodes were prepared by a flow-directed self-assembly strategy. Nitrogen doping validly exploit graphene's utilization by preventing graphene sheets' stacking and introducing pseudocapacitance. The PEDOT component not only improves the hybrids' conductivity and decreases NG's stacking, but also plays the role of binders to induce the hybrids to be free-standing film through simple vacuum filtration. The doping of nitrogen atoms and PEDOT endow the hybrids film with superior hydrophilicity, high conductivity, as well as good electrochemical capacitance (536 F g −1 at 0.5 A g −1 ). The hybrids films are simultaneously used as electrode materials, current collector, and mechanical support to fabricate flexible supercapacitor with the specific capacitance of 206 F g −1 at 0.25 A g −1 . Moreover, the NG/PEDOT hybrids present giant potential in the electrochemical sensor area on account of its superior catalytic properties, hydrophilicity, and conductivity. The NG/PEDOT hybrids modified electrode presents high sensitivity (0.9 μA mM −1 cm −2 ), with a linear range from 0.2 μM to 90 μM, a detection limit of 54 nM (S/N=3) for dopamine detection. Graphical abstract: Image, graphical abstract